Lentinan -triggered butyrate-producing bacteria drive the expulsion of the intestinal helminth Trichinella spiralis in mice - Jin, Xuemin; Liu, Yi; Vallee, Isabelle; Karadjian, Gregory; Liu, Mingyuan; Liu, Xiaolei (Frontiers in Immunology, 2022)
Trichinellosis caused by Trichinella spiralis is a serious zoonosis with a worldwide distribution. Lentinan (LNT) is known to modulate the intestinal environment with noted health benefits, yet the effect of LNT against intestinal helminth is unknown. In our study, we first observed that LNT could trigger worm expulsion by promoting mucus layer functions through alteration of gut microbiota. LNT restored the abundance of Bacteroidetes and Proteobacteria altered by T. spiralis infection to the control group level. Interestingly, LNT triggered the production of butyrate. Then, we determined the deworming capacity of probiotics (butyrate-producing bacteria) in mice. Collectively, these findings indicated that LNT could modulate intestinal dysbiosis by T. spiralis, drive the expulsion of intestinal helminth and provided an easily implementable strategy to improve the host defence against T. spiralis infection.